Aneurisma arterial coronario secundario a enfermedad de Kawasaki - Moreno-Martínez, Francisco L.; Gómez Guindal, José A.; Martínez-Quintana, Efrén; Nápoles Lizano, Mario E. (CorSalud, 2022)
Aneurisma arterial coronario secundario a enfermedad de Kawasaki